2020
DOI: 10.1126/science.abd2321
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of a shared antibody response to SARS-CoV-2

Abstract: Molecular understanding of neutralizing antibody responses to SARS-CoV-2 could accelerate vaccine design and drug discovery. We analyzed 294 anti-SARS-CoV-2 antibodies and found that IGHV3-53 is the most frequently used IGHV gene for targeting the receptor-binding domain (RBD) of the spike protein. Co-crystal structures of two IGHV3-53 neutralizing antibodies with RBD, with or without Fab CR3022, at 2.33 to 3.20 Å resolution revealed that the germline-encoded residues dominate recognition of the ACE2 binding s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

69
810
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 610 publications
(885 citation statements)
references
References 50 publications
(81 reference statements)
69
810
2
4
Order By: Relevance
“…There are situations that are anticipated to increase the frequency of encounters between SARS-CoV-2 and antibodies that could impact the emergence of antibody resistance. (3,18,19). These findings imply a degree of homogeneity the among neutralizing antibodies that are generated in different individuals.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There are situations that are anticipated to increase the frequency of encounters between SARS-CoV-2 and antibodies that could impact the emergence of antibody resistance. (3,18,19). These findings imply a degree of homogeneity the among neutralizing antibodies that are generated in different individuals.…”
Section: Discussionmentioning
confidence: 80%
“…The low levels of somatic hypermutation and repetitive manner in which similar antibodies (e.g. those based on IGHV3-53 (3,18,19) have been isolated from COVID19 convalescents suggests that potently neutralizing responses should be readily elicited. Paradoxically, a significant fraction of COVID19 convalescents, including some from whom potent neutralizing antibodies have been cloned, exhibit low levels of plasma neutralizing activity (3,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the majority of the ACE2 blocking antibodies-including CB6 16 , B38 17 , CV30 18 , CC 12.1 19 , CC 12.3 19 and REGN10933 14 -adopt a similar orientation when bound to RBD. Each of these antibodies belong to the immunoglobulin heavy chain variable region genes (IGHV) 3 germline that is the most frequently used IGHV gene among the known SARS-CoV-2 neutralizing antibodies 22 . The neutralizing antibody P2B-2F6 15 which is based on the IGHV4-38 gene, on the other hand, interacts with RBD at about a 90 degree angle from the previous group.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody EY6A (6zdh.pdb) binds the RBD in the region of the cryptic epitope described by Wilson and collaborators 35 (Figure 4). Importantly, our predicted patch (365)YSVLYN(370)-(384)PTKLN(388) covers a significant part of the epitope.…”
Section: A B D E Cmentioning
confidence: 91%
“…On the one hand, this may be important considering the fact that RBD can also be the target on non-neutralizing antibodies, e.g. 3022 35 . Indeed, using cocktails of antibodies to target different regions of S has recently been proposed as a viable therapeutic option 36 .…”
Section: A B D E Cmentioning
confidence: 99%